ASSESSMENT OF THE CURRENT STATE OF THE POPULATION OF THE SPECIES RHEUM WITTROCKII LUNDSTR. FLORA OF THE SOUTH-EAST OF KAZAKHSTAN (Eurasian Journal of Ecology, 2025)
This article is devoted to the study of the current state of the Rheum wittrockii Lundstr. species population, floristic composition and ecological characteristics of this species populations in the Uzynkara and Ile-Alatau ridges, Almaty region. Rheum wittrockii Lundstr., an ancient genus of the Neogene period of Asian origin, includes 9 species in Kazakhstan. Three natural populations of Rheum wittrockii Lundstr. were studied in various ecological and phytocenotic conditions of the Uzynkara and Ile-Alatau ridges. Rheum wittrockii in the studied areas are distributed in the middle part of the forest belt of mid-mountains where they exhibit high adaptive abilities, which indicate their ecological plasticity, are characterized by high rates of seed and vegetative reproduction, are resistant to diseases, retain a characteristic habitus in culture, are highly decorative and can be recommended for use in landscaping. In most populations of Rheum wittrockii, generative and virginal individuals prevailed, less often pregenerative individuals played the main role in the population. As a result of the monitoring, the population size in the studied area has been rapidly declining in recent decades, which requires necessary measures to preserve and restore the population size of Rheum wittrockii Lundstr. species in the studied area. To maintain and ensure normal life of Rheum wittrockii Lundstr. populations in the studied areas, it is necessary to standardize the degree of anthropogenic impacts. The main anthropogenic threats to the rare species Rheum wittrockii Lundstr. are overgrazing, habitat disturbance, which have led to a reduction in populations, which will require conservation strategies such as habitat monitoring.Keywords: natural populations, plant communities, rare species, Uzynkara. Ile Alatau